Espiritualidade, religiosidade e sentido do sofrimento na vida de cuidadores de crianças e adolescentes com câncer - Chaves, Amanda Karla Diniz Liberato (2023)
Several studies indicate that religion and spirituality can have psychotherapeutic effects on human being. Thus, this work seeks to identify the role of spirituality/religiosity in the experience of caregivers of children and adolescents with cancer. Therefore, a qualitative research was carried out, using semi-structured interviews with the caregivers, which contained questions about their religiosity and experience as a caregiver, in addition to a sociodemographic questionnaire. Eighteen caregivers were interviewed, aged between 24 and 56 (M=37,88; SD= 9,24), being 94,45% women and 5,55% men. The interviews were transcribed to the Microsoft Word processor (2010) and analyzed using the Iramuteq software, using the word cloud, descending hierarchical classification and similarity analysis. The results suggested that religiosity and spirituality are important during the treatment period, considering that they help caregivers to find a meaning to continue caring for the children/adolescents with cancer. Furthermore, it is the attitudinal values that most appear as a source of meaning for caregivers. The results were discussed by Viktor Frankl’s Logotherapy and Existential Analysis and indicated that most participants had a religious belief and spiritual practices that helped them to deal with moments of suffering; the importance of the family support network was verified and it was noticed that most caregivers find meaning through the realization of attitudinal values.